PHYSICAL-MECHANICAL PROPERTIES OF COMPOSITE MATERIALS BASED ON VERMICULITE, BAZALT, WOLLOSTANITE, AND POLYETHYLENE P-Y 342 AND POLYAMIDE PA-6 - Dusanov, Ravshan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article describes how to fill polypropylene with oligomers containing nitrogen, phosphorus, and metal to produce heat-resistant and mechanically strong thermoplastic composite materials. Polypropylene compositions, solution flow index determination, viscometric methods, bending strength determination using two-support methods, and bending, Charpy impact strength measurement methods are all discussed. The amount of filler used in the production of composite materials based on basalt mineral from polyvinyl chloride ranged from 1 mass part to 5 mass parts. The physicomechanical characteristics of the developed composite materials revealed that increasing the amount of filler decreases the material's fluidity. The optimal amount of basalt-containing fillers in the composite material, according to the results, is 5 parts by mass.